(untitled) (Zoo Botanica, 2025)
The agricultural sector is under growing pressure to improve crop yields and production efficiency in order to meet the escalating demands for food worldwide. Weeds, crop pathogens, and insect pests remain major biotic constraints, with weeds persistently ranked among the most detrimental factors limiting crop yields. Weeds pose a persistent challenge in crop husbandry, competing aggressively with cultivated plants for essential growth resources including soil moisture, nutrients, and sunlight. Such competition reduces crop yields, besides affecting biodiversity. Conventional weed management practices rely heavily on synthetic herbicides, have raised serious concerns. These concerns include environmental contamination, the evolution of herbicide-resistant weed populations, and harmful impacts on non-target organisms such as pollinators and beneficial soil microorganisms. Therefore, there is a growing demand to explore sustainable weed management alternatives that safeguard agronomic productivity while preserving ecological balance. Conventional herbicide-based weed management has raised concerns due to environmental contamination, the emergence of herbicide-resistant weed biotypes, and detrimental impacts on non-target organisms. These challenges have accelerated the search for sustainable weed management strategies. Biological approaches, such as bioherbicides derived from fungi, bacteria, and allelopathic plants, provide environmentally friendly options consistent with the principles of sustainable agriculture. Among these, essential oils—rich in phytotoxic terpenoids—demonstrate fortified potential as natural alternatives due to their selectivity and minimal environmental impact. Biological approaches suppress weeds through natural allelopathic and microbial mechanisms, enhance agro-biodiversity, improve soil health leading to reduced reliance on synthetic herbicides. The present article underscores the potential of integrating bioherbicides and other allelopathic agents into weed management programs to boost sustainable crop production systems and strengthen ecological resilience